Effects of fatty acids on endothelial cells: inflammation and monocyte adhesion - Grenon, S. Marlene (2012)
BACKGROUND: Diet is known to have an important impact on cardiovascular health. n-3 FAs, found in high quantity in fish oil, have demonstrated beneficial effects in patients with coronary artery disease. The role of n-6 FAs remains more controversial. The objective of this study was to examine the effect of arachidonic acid (AA), an n-6 FA, and eicosapentanoic acid (EPA), an n-3 FA, on the interaction between monocytes and endothelial cells. DESIGN: We used a cellular model of endothelial cells (EA.hy.926) and monocytes (human leukemic myelomonocytic U937). Confluent endothelial cells were treated with AA or EPA, in the presence of TNF-α or vehicle-alone for either 4 or 24 hours. Adhesion of monocytes to the endothelial monolayer was performed. For gene expression, reverse transcription, followed by real-time quantitative polymerase chain reaction, were performed. RESULTS: There was a significant increase in adhesion of monocytes to the endothelial monolayer in the presence of n-6 FAs, both in the presence or absence of TNF-α at 4 and 24 hours. The adhesion of monocytes to the endothelial monolayer was decreased with n-3 FAs at 24 hours. ICAM-1, VCAM, E-Selectin, IL-6 and TNF-α were significantly increased in endothelial cells treated with n-6 FAs. CONCLUSIONS: We conclude that AA increases inflammation and enhances the ability of endothelial cells to bind monocytes in vitro. EPA leads to a decrease in the ability of EA.hy.926 to bind monocytes, although the effect appears more modest. Taken together, these data indicate that the n-6 FA AA could potentiate inflammation and early events of atherosclerosis.